IMPACT OF AI AND LSTM-BASED SCRIPTWRITING PLATFORMS ON BUSINESS-PROCESSES OPTIMIZATION OF CONTROL SYSTEMS IN FILM INDUSTRY - Aidarbekov, A.; Ibraiymov, A.; Murzabekova, G.; Aidarbekova, A.; Satybaldy, N. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The optimization of film production through global standards and advanced software remains underutilized in CIS countries due to regional specifics and language barriers. Consequently, inefficiencies in resource management, time allocation, and quality control persist. The film industry’s rapid development has led to unstructured business processes that hinder optimization and standardization. This research aims to develop a business process management model utilizing artificial intelligence (AI) and recurrent neural networks (RNNs), particularly long short-term memory (LSTM) networks, to enhance scriptwriting automation. The proposed AI-driven platform facilitates script generation, empowering filmmakers by reducing dependency on experienced screenwriters. This paper presents practical solution for potential impact on filmmaking efficiency